Mediterranean diet adherence and metabolic syndrome in US adolescents. (19th May 2021) - Kim, Roy J.; Lopez, Rocio; Snair, Megan; Tang, Anne
Abstract: The Mediterranean diet (MD) has been found to lower the risk of heart disease, stroke, and diabetes in adults. Little is known about its acceptance and relationship to cardiovascular risk markers in US adolescents. Using data from the National Health and Nutrition Examination Survey, years 2007–2014, we performed a cross-sectional analysis of adherence to the Mediterranean diet among a representative sample of US adolescents ( n = 4223), factors that influence adherence, and whether adherence is associated with cardiometabolic risk factors including metabolic syndrome. MD adherence was calculated using the KIDMED scoring system. We found that overall MD adherence was very low among US adolescents, with Mexican American youths having higher adherence compared to other groups. Higher income was associated with greater adherence. There was low intake of key MD foods including olive oil and finfish. The unadjusted prevalence of metabolic syndrome was 6.6%. MD adherence was not associated with metabolic syndrome.